Analysis of Class Teacher Difficulties in Thematic Learning at Madrasah Ibtidaiyah - Ricka Tesi Muskania (UIN Siber Syekh Nurjati Cirebon, 2019)
AbstractThis study was intended to describe the difficulties of first grade MI Al-Ikhwah Pontianak teachers in planning, implementing, and conducting assessments in thematic learning. This research adopts descriptive qualitative methods. Data collection techniques used were observation, interviews, and documentation. The data sources of this study were first grade teachers and Head of Madrasah Ibtidaiyah Al-Ikhwah. Data analysis techniques include data reduction, data presentation, and conclusions. The results showed that in the planning stage, teachers found difficulty in composing lesson plan which based on the conditions of the students. Besides, they also found difficulty in sorting out the basic competencies in the syllabus and lesson plans. At last, teachers found difficulty in preparing appropriate learning media for thematic learning. Meanwhile, at the implementation stage, the teacher found difficulties in adjusting the time allocation of learning instruction, difficult to facing the demands of completing one learning in one meeting, adjusting basic competencies with learning material in half a day, synergizing the delivery of objectives and activities as a whole with the allocation of time, and applying a scientific approach in learning. Whereas, at the teacher evaluation stage, it is difficult to use assessment instruments based on the condition of the students. Besides, the teachers found it difficult to adjust anecdotal notes with the assessment of the 2013 curriculum report cards. Therefore, the research findings should be used as an evaluation material for classroom teachers in applying thematic learning in classroom activities.Keywords: teacher difficulties, thematic learning, 2013 curriculum.AbstrakPenelitian ini bertujuan untuk mendeskripsikan kesulitan guru kelas satu MI Al- Ikhwah Pontianak dalam merencanakan, melaksanakan, dan melakukan penilaian dalam pembelajaran tematik. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi. Sumber data penelitian ini adalah guru kelas satu dan Kepala Madrasah Ibtidaiyah Al- Ikhwah. Teknik analisis data yang digunakan meliputi reduksi data, penyajian data, dan kesimpulan. Hasil penelitian menunjukkan bahwa pada tahap perencanaan guru mengalami kesulitan dalam menyusun RPP sesuai kondisi dan lingkungan peserta didik, guru sulit memilah kembali kompetensi dasar pada silabus dan RPP, dan guru sulit menyiapkan media pembelajaran yang tepat dalam pembelajaran tematik. Sementara itu, pada tahap pelaksanaan guru mengalami kesulitan dalam menyesuaikan alokasi waktu dengan pembelajaran, sulit menghadapi tuntutan penyelesaian satu pembelajaran dalam satu kali pertemuan, sulit menyesuaikan KD dengan materi pembelajaran dalam setengah hari, sulit mensinergikan penyampaian tujuan dan kegiatan secara keseluruhan dengan alokasi waktu, dan sulit mengaplikasikan pendekatan saintifik dalam pembelajaran. Â Sedangkan pada tahap penilaian guru sulit menggunakan instrumen penilaian keterampilan dengan keadaan peserta didik dan guru sulit menyesuaikan catatan anecdot dengan penilaian pada raport kurikulum 2013. Oleh karena itu, temuan-temuan penelitian tersebut hendaknya dapat dijadikan sebagai bahan evaluasi bagi guru kelas dalam menerapkan pembelajaran tematik di kelas.Kata kunci: kesulitan guru, pembelajaran tematik, kurikulum 2013.